PERAN STRATEGIS GURU AKIDAH AKHLAK DALAM PENGEMBANGAN KARAKTER DISIPLIN SISWA DI MA SABDA RIA NADA BESUKI SITUBONDO - Imam Hendri Yanto; Ahmad Khumaidi; Mahfudz Sulaiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the strategic role of Aqidah Akhlak teachers in shaping and developing students’ discipline character at MA Sabda Ria Nada Besuki Situbondo. The primary focus of this research is directed toward how teachers design, implement, and evaluate efforts to foster discipline through both classroom learning processes and extracurricular activities. This study employs a qualitative approach with a descriptive design. The research subjects include Aqidah Akhlak teachers, students, and relevant school stakeholders. Data collection techniques consist of observation, in-depth interviews, and documentation, while data analysis is conducted through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that Aqidah Akhlak teachers play a significant role as educators, role models, and mentors in instilling disciplinary values. The strategies implemented include habituation of disciplined behavior, providing exemplary conduct, reinforcing values through instructional materials, and consistently enforcing rules. In addition, support from the school environment and student involvement also influence the success of character development. However, several challenges were identified, such as differences in students’ backgrounds and varying levels of awareness. Therefore, continuous synergy between teachers, schools, and family environments is necessary to optimize the development of students’ discipline character.